Potential Pathways for Mycobacterium Bovis Zoonotic Transmission to Humans - England, Lauren (My University, 2012)
Veterinary Services, a branch of Animal Plant Health Inspections Services, has the responsibility to protect our nation’s animals and animal products through disease control and eradication programs, surveillance and monitoring. During the course of my experience working with Veterinary Services, I learned about program diseases and the different ways veterinary medical field officers and epidemiologists work together to control, monitor and survey these diseases. Veterinary Services has been working to eliminate bovine tuberculosis in the United States since the early 1900’s. The Bovine Tuberculosis Eradication Program has been largely successful but tuberculosis keeps resurfacing in pockets around the U.S. leading to the conclusion that there must be a wildlife reservoir. Mycobacterium bovis is the cause of bovine tuberculosis and is considered a zoonotic pathogen. M. bovis has been reported to infect a wide range of host species including cattle, goats, sheep, pigs, cats, dogs, bison, badgers, possums, antelopes, elephants, seals, and humans(1). Through my experiences working with Veterinary Services, I was able to learn about the bovine tuberculosis eradication program and to explore different avenues in which M. bovis could be transmitted to humans. My report discusses the potential pathways for M. bovis zoonotic transmission to humans and my experiences working with Veterinary Services.
Keywords: Zoonotic Transmission; Mycobatcerium Bovis; USDA Veterinarian Services; Zoonotic Pathogen; Bovine Tuberculosis; Public Health (0573)